2021
DOI: 10.17352/2455-815x.000109
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of advanced sorghum (Sorghum bicolor L. Moench) hybrid genotypes for grain yield in moisture stressed areas of Ethiopia

Abstract: Sixty two advanced hybrid sorghum varieties were evaluated in three environments, Kobo (KB), Sheraro (SH) and Mieso (MS) during 2019 of the main season. The objective of this study was to evaluate sorghum hybrids for production in drought stressed areas of Ethiopia. The experiment was piloted using a randomized complete block design with two replications. The result of over sites showed for grain yield, environments, environment by block and genotype by environment interaction effect highly signifi cant variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
0
0
Order By: Relevance
“…The study was showed using eighty-four hybrid lines across six locations to identify the most stable and high yielding genotypes. The results specified that yield performance of sorghum genotypes were influenced by genotype, the environments and GEI effect [15]. Similarly, the study as showed using eighty-four hybrid lines across six locations to identify the most stable and high yielding genotypes.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…The study was showed using eighty-four hybrid lines across six locations to identify the most stable and high yielding genotypes. The results specified that yield performance of sorghum genotypes were influenced by genotype, the environments and GEI effect [15]. Similarly, the study as showed using eighty-four hybrid lines across six locations to identify the most stable and high yielding genotypes.…”
Section: Introductionmentioning
confidence: 81%
“…Desert locust infestation in different part of country [14]. Lack of high yield and stable varieties across diverse environments is a challenge of sorghum production yield loss in Ethiopia [15]. Also, the yield potential of variety on the farmer field and on research station varies which impact on yield reduction.…”
Section: Introductionmentioning
confidence: 99%